Insights into enhanced removal of U(VI) by melamine sponge supported sulfurized nanoscale zero-valent iron. (20th December 2021) - Tang, Hao; Zhang, Shu; Pang, Hongwei; Wang, Jiaqi; Wang, Xiangxue; Song, Gang; Yu, Shujun
Abstract: Radioactive pollutants have always been the top priority in wastewater, and searching a green and efficient treatment technology remains a significant challenge. In this study, a novel melamine sponge supported sulfurized nanoscale zero-valent iron (MS@S-NZVI) material with high dispersion was firstly designed to effectively capture U(VI) from water environment. The target material could retain its original structure in water due to the excellent mechanical strength of MS, which greatly inhibited the aggregation of S-NZVI. A series of characterization techniques, such as SEM, XRD, FTIR, TGA and XPS, had proved the effective synthesis and excellent structural properties of the MS@S-NZVI. The faster reaction equilibrium (<1 h) and higher maximum adsorption capacity (180 mg/g at pH = 5 and 298 K) exposed the perfect performance of target material in the elimination of U(VI). In addition, further researches in different water systems exhibited that MS@S-NZVI had a significant U(VI) removal rate in simulated wastewater systems. Finally, the removal process of MS@S-NZVI to U(VI) could be divided into three pathways through the XPS technique, adsorption and reduction were the main reaction mechanisms. This study provides a new insight into the utilization of melamine sponge and a prospect for the practical application of S-NZVI in the removal of radionuclide. Graphical abstract: Image 1 Highlights: Melamine sponge was used to support S-NZVI for the first time. The structure of sponge enabled MS@S-NZVI to disperse fully in water. The practical application potential of MS@S-NZVI was confirmed. Adsorption and reduction were the main reaction mechanisms.